TRANSFORMASI PROFESI GURU SD UNTUK MENINGKATKAN KETERAMPILAN PESERTA DIDIK PADA ABAD 21 MELALUI PEMBELAJARAN DIGITAL - Jibrael Leo Tallo; Elsa Lodribka Tampani; Graziana Maria Jawa Sogen; Irene Yuningsih Saputri Luthfi; Fitri Marselina Sakbana; Priandy Benu; Hiwa Wonda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid advancements in information and technology have had a significant impact on daily life, including on education today. The objective of this study is to analyze the role and transformation of teachers regarding the effective use of technology, as well as how this can help enhance students skills in line with the demands of the 21st century. This study employs a qualitative method with a descriptive approach based on literature review (library research). The results of the study indicate that the role of teachers has shifted from being primarily focused on conveying information to that of a facilitator, mentor, and manager of digital based learning. Digital learning offers significant opportunities to enhance students critical thinking, communication, collaboration, and creativity skills through interactive and innovative activities. Therefore, teachers digital literacy plays a crucial role in the success of 21st- century learning.